2012
DOI: 10.1007/s40065-012-0025-2
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental relations in simple and 0-simple semihypergroups of small size

Abstract: We consider the fundamental relations β and γ in simple and 0-simple semihypergroups, especially in connection with certain minimal cardinality questions. In particular, we enumerate and exhibit all simple and 0-simple semihypergroups having order 3 where β is not transitive, apart of isomorphisms. Moreover, we show that the least order for which there exists a strongly simple semihypergroup where β is not transitive is 4. Finally, we prove that γ is transitive in all simple semihypergroups, and determine nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…A subhypergroup K of a hypergroup (H, •) is said to be conjugable if it satisfies the following property: for all x ∈ H, there exists x ∈ H such that xx ⊆ K. The interested reader can find all relevant definitions, many properties, and applications of fundamental relations, even in more abstract contexts, also in [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Basic Definitions and Resultsmentioning
confidence: 99%
“…A subhypergroup K of a hypergroup (H, •) is said to be conjugable if it satisfies the following property: for all x ∈ H, there exists x ∈ H such that xx ⊆ K. The interested reader can find all relevant definitions, many properties, and applications of fundamental relations, even in more abstract contexts, also in [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Basic Definitions and Resultsmentioning
confidence: 99%
“…In our preceding papers [5,7,12] we faced the study of simple semihypergroups where the fundamental relation β is not transitive, in all subsemihypergroups of size ≥ 3. These semihypergroups, which we called fully simple, own a right (or left) zero scalar element and all their hyperproducts have size ≤ 2.…”
Section: Discussionmentioning
confidence: 99%
“…The six semihypergroups in Example 3.5 belong to the list of fourteen 0-semihypergroups of size 3 where the relation β is not transitive [12,Thm. 5.6].…”
Section: The Class Of G 0 -Semihypergroupsmentioning
confidence: 99%
See 1 more Smart Citation
“…The semihypergroups are the simplest algebraic hyperstructures that possess the properties of closure and associativity. Some scholars have studied different aspects of semihypergroups [2,5,8,9,19,20,[22][23][24] and interesting problems arise in the study of their so-called fundamental relations [1,7,16,21,25], which leads to analyzing the conditions for their transitivity, and minimal cardinality problems. In [16] the authors found all simple and zero-simple semihypergroups of size 3 , such that the fundamental relation β is not transitive, apart from isomorphisms.…”
Section: Introductionmentioning
confidence: 99%